The Role of Muslim Rohingya Refugee Community-Based Organizations in Malaysia - Khairi, Aizat (Universitas Islam Internasional Indonesia (UIII), 2024)
The Rohingya refugee crisis has spurred the formation of community-based organizations (CBOs) among Muslim Rohingya refugees in Malaysia. This qualitative research explores the role and impact of these organizations within the refugee community. By employing a mixed-methods approach, including semi-structured interviews and content analysis, the study delves into the motivations, activities, challenges, and outcomes of Rohingya CBOs. The findings suggest that these CBOs play a critical role in bridging the gap between formal assistance and the unique needs of the Rohingya population in Malaysia. They offer vital services, foster a sense of belonging, and contribute to mental well-being. However, challenges related to resources and sustainability are apparent. This research contributes to a better understanding of refugee agencies and grassroots initiatives. It sheds light on the significance of CBOs as agents of change, amplifying the voices and actions of refugees themselves. The study's findings show that both policy and practice support and empower refugee communities.